Մեսխեթցի թուրքերի կազմավորումը Սամցխեի ու Ջավախքի ժողովրդագրական շարժի համապատկերում - Կարո Գալոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В данной статье изучается этнический и религиозный состав населения исторических регионов Самцхе и Джавахк и демографические изменения в промежутке времени с установления османской власти в конце XVI века до 1939 года. This article examines the ethnic and religious composition of the population of historical regions Samtskhe and Javakheti and demographic changes in the period from the late 16th century, when those regions were conquered by the Ottomans, to 1939.
Keywords: History; Armenian Diaspora; Christianity; History of the Armenian Church